AKTIVITAS ANTIOKSIDAN EKSTRAK AIR DAUN TEH (CAMELLIA SINENSIS L.O. KUNTZE) - NIKEN NINDITA , ANNA
The antioxidant effect of black tea and green tea (Camellia sinensis L.O. Kuntze) had been studied in Swiss Webster male mice. The antioxidant activity was determined by test against superoxide dismutase (SOD) activity and lipid peroxidation. Black tea water extract (EATHt) and green tea water extract (EATHj) increased SOD activity significantly (p<0.01) i.e., 0.85 unit/gHb for EATHt at 40 mg/kg bw; 0.91 and 1.08 unit/gHb for EATHj at 30 and 60 mg/kg bw, respectively, compared to that of control (0.33 unit/gHb). By using liver as an target organ, EATHt and EATHj increased total antioxidant activity (TAA) significantly (p<0.01) i.e., 111.39% for EATHt at 40 mg/kg bw; 116.73, 161.16, and 168.46 % for EATHj at 15, 30, and 60 mg/kg bw, respectively, compared to that of control (70.86%) on the test without induction of free radical formation; while on the test with induction of free radical formation, those extracts showed TAA significantly (p<0.01) of 98.30% for EATHt 40 mg/kg bw; and 112.11, 124.75, and 130.27 % for EATHtj 15, 30, and 60 mg/kg bw, respectively, compared to that of control (67.71%). By using kidney, on the test without induction of the free radical formation, EATHt and EATHj increased TAA significantly (p<0.01) i.e., 30.54 and 32.24 % for EATHt 20 and 40 mg/kg bw; 32.63, 34.26, and 34.29 % for EATHj 15, 30, and 60 mg/kg bw, respectively, compared to that of control (20.13%). On the test with induction of free radical formation in the same organ, EATHt at 30 and 60 mg/kg bw increased TAA significantly (p<0.01) i.e., 33.44 and 36.08 %, respectively, compared to that of control (21.54%). Based on these results, it can be concluded that EATHj has stronger antioxidant activity than EATHt.